Foreign Direct Investment Perspective through Foreign Direct Divestment - Maček, Anita (IntechOpen, 2021)
Since the turn of the century, the liberalization of capital markets has caused exponential growth of foreign direct investment (FDI). However, developments in recent years have shown that countries have placed limitations on foreign investors. In addition, dynamic economic developments in the surge of financial and economic crisis and later have clearly exposed the possibility that FDI will change course and result in foreign direct divestment. This book looks at specific country experiences related to FDI as well as determinants of FDI that could be connected to the new course of divestment.